Effects of 20 mol% Fe, Co, Ni additions on phase formation, microstructure and mechanical properties of TaCx (x = 0.5, 0.55, 0.6, 0.7) ceramics. (February 2021) - Li, Zhonghua; Shi, Faqiang; Liu, Limeng; Vleugels, Jozef; Huang, Shuigen
Abstract: TaCx (x = 0.5, 0.55, 0.6, 0.7) ceramics with 20 mol% Fe, Co or Ni addition were prepared by hot pressing TaC and Ta powder mixtures at 1800 °C. X-ray diffraction, scanning electron microscopy, transmission electron microscopy, high resolution transmission electron microscopy, X-ray energy dispersive spectroscopy and selected area electron diffraction were used to investigate the constituent phases and microstructures of the composites. Vickers hardness, flexural strength and fracture toughness were measured. Intermetallic compounds Fe7 Ta3, Co2 Ta and Ni3 Ta were formed due to reactions of Fe, Co and Ni with Ta. The remaining TaC and Ta reacted to form hexagonal Ta2 C, rhombohedral ζ-Ta4 C3-z or cubic TaCy depending on the overall C:Ta ratios. The microstructure of the TaC0.5 –20 mol% Fe, Co, Ni compositions (where C:Ta = 0.5) were composed of intermetallics and fine anisotropic Ta2 C and ζ-Ta4 C3-z grains. As the C:Ta ratio increased to 0.55–0.7, the ζ-Ta4 C3-z and TaCy grains were enlarged in size and equiaxed in the TaC0.55 -, TaC0.6 -, and TaC0.7 –20 mol% Fe, Co, Ni compositions. Addition of Ni instead of Fe and Co benefitted to refine microstructures of the composites. The TaC0.5 –20 mol% Fe, Co, Ni compositions had good flexural strength (580-650 MPa) and fracture toughness (9.3–9.5 MPa·m 1/2 ) due to growth of fine lamellar grains, despite the high Ta2 C content. Highlights: TaCx (x = 0.5, 0.55, 0.6, 0.7) ceramics with 20 mol% Fe, Co or Ni addition. Ta2 C, ζ-Ta4 C3-z or cubic TaCy formed depending on overall C:Ta ratio. Addition of Ni instead of Fe and Co benefitted to refine microstructures. The TaC0.5 compositions were composed of fine anisotropic Ta2 C and ζ-Ta4 C3-z . Good strength and toughness of TaC0.5 compositions despite high Ta2 C content.